2006
DOI: 10.2146/ajhp050538
|View full text |Cite
|
Sign up to set email alerts
|

ASHP national survey of pharmacy practice in hospital settings: Dispensing and administration—2005

Abstract: Safe systems continue to be in place in most hospitals, but the adoption of new technology is changing the philosophy of medication distribution. Pharmacists are continuing to improve medication use at the dispensing and administration steps of the medication-use process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
109
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(112 citation statements)
references
References 14 publications
1
109
0
2
Order By: Relevance
“…19 In 2005, the American Society of Health-System Pharmacists surveyed a sample of 510 hospitals and found slightly higher adoption of ADM (72 percent), ROBOT (15 percent), EMAR (21 percent), and BarA (9 percent). 20 This study reported only bivariate associations between health IT and hospital size. We attribute discrepancies between these surveys and our results to different definitions of adoption and our larger sampling frame.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 93%
“…19 In 2005, the American Society of Health-System Pharmacists surveyed a sample of 510 hospitals and found slightly higher adoption of ADM (72 percent), ROBOT (15 percent), EMAR (21 percent), and BarA (9 percent). 20 This study reported only bivariate associations between health IT and hospital size. We attribute discrepancies between these surveys and our results to different definitions of adoption and our larger sampling frame.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 93%
“…3 The frequency of administration errors ranges from 2.4% to 47.5%, depending on the drug distribution system in place. 4 In the United Kingdom, a recent report by the National Patient Safety Agency (NPSA) indicated that 56.5% of reported errors associated with severe harm or death occurred at the administration step. 5 Medication orders require the drug, dose, rate, route, frequency, and, when appropriate, duration to be explicit and specific to the needs of the patient in order to achieve the desired outcome.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most medicines for inpatient use are dispensed and prepared in a centralized pharmacy; however, some hospitals have satellite pharmacies in patient care areas. 3,4 Some medicines are kept in the patient care area (e.g., on the wards and in intensive care units and the emergency department), but the use of such medicines is limited for safety reasons in some hospitals with unit dose drug distribution systems. Some patients bring their own medicines for use in the hospital, but this practice is limited for safety reasons in some hospitals.…”
mentioning
confidence: 99%
“…Pedersen et al [10] examined 1173 hospital pharmacies in the USA in to assess the role of the pharmacist in the respective drug distribution system, and concentrated on the respective administrative effort associated with www.ljm.org.ly distribution of the drugs. A differentiation was made between the conventional manual unit dose and stationary fully automatic robot technology.…”
Section: Introductionmentioning
confidence: 99%